Bibliometric analysis of real-time PCR-based pathogen detection in plant protection research: a comprehensive study - Lal, Priyanka; Tiwari, Rahul Kumar; Kumar, Awadhesh; Altaf, Muhammad Ahsan; Alsahli, Abdulaziz Abdullah; Lal, Milan Kumar; Kumar, Ravinder (Frontiers in Plant Science, 2023)
The discovery of real-time PCR-based plant pathogen detection and gene expression analysis has revolutionized the field of plant protection. Researchers across the globe are using this technique for the raid and sensitive detection of several fungal, viral bacterial, and phytoplasma-infected plant samples on a larger scale. This study analyzed the worldwide research on real-time PCR-based pathogen detection carried out from 2001 to 2021 that has been employed for any diagnostic assay or gene expression level studies. The 'Dimensions' database has been specifically used for literature retrieval. The visualization software for bibliometric analysis demonstrated the major publishing journal, the institutions involved in these investigations, the esteemed leading journals, prominent authors, and most cited articles along with the major common keywords. The study's search query was based on the conjunction 'AND'. The dataset was obtained through fourteen distinct search queries, and the results consistently indicated a significant increase in the number of scholarly publications over time. This trend suggests that there is a growing interest and investment in research within the field of study under consideration. This finding highlights the importance of ongoing investigation and development in the field and the potential for continued advancements in knowledge and understanding. The leading journal which published the relevant papers was Plos One followed by BMC Genomics and Phytopathology. The European Journal of Plant Pathology received the most citations, followed by BMC Genomics and Fungal Genetics and Biology. United Nations and China had publications that had the highest number of citations and publications. Network visualization map of the co-authorship analysis revealed interesting data of 2636 authors, out of which 50 surpassed the level threshold. Altogether, the analysis suggested that the research on RT-PCR-based pathogen detection is booming and it requires strengthening using modern diagnostic tools and collaboration among well-equipped labs.